Implementasi Restorative Justice dalam Sistem Peradilan Pidana Indonesia dalam Tinjauan Keadilan Substantif - Ismawanto Somantri (Universitas Cokroaminoto Yogyakarta, 2026)
The Restorative Justice process constitutes an alternative mechanism for resolving criminal cases outside the court by involving offenders, victims, and relevant stakeholders to reach a fair and recovery-oriented agreement. However, in practice, its implementation still faces challenges, including the dominance of a retributive paradigm among law enforcement officials, fragmented and non-integrated regulations, and the potential risk of re-victimization of victims. This study employs a normative juridical method through literature review with qualitative analysis. The findings indicate that the implementation of Restorative Justice in the Indonesian criminal justice system reflects a shift from a retributive paradigm toward a restorative approach focused on recovery, in line with the principle of substantive justice. Its legal basis is regulated through internal regulations of the police (Perpol 8/2021), the prosecution service (Perja 15/2020), and the Supreme Court (PERMA 1/2024). Strengthening the legal umbrella, training officials, and empowering the role of the community to realize substantive justice that is oriented towards recovery are the solutions.